Clinical profile of patients with acute organophosphorus poisoning in a tertiary care hospital - Bhattad, Prashant H.; Bhattad, Sneha P. (International Journal of Research in Medical Sciences, 2022)
Background: Organophosphorus compound poisoning episodes are relatively common in occurrence in this part of the world and are associated with high levels of morbidity as well as death, at times despite competent care. The present study was conducted to profile clinically the patients admitted with history of acute organophosphorus poisoning. Methods: This prospective observational study was conducted between September 2017 and October 2019 at four hospitals with intensive care units in a city in central-west India region, wherein clinically relevant details of patients admitted with history of acute organophosphorus poisoning were noted and analysed. Results: Out of 160 participants studied, males (58.75%) and those between 21-30 years age group (45.0%) were affected more. Suicidal attempt was the commonest mode (97.5%). Majority of the participants belonged to severity grade II (45%); with severity grades found directly related to longer hospital stay and death. Constriction of pupils (76.25%) was the commonest clinical sign observed. The death rate was calculated to be 21.25%, with monocrotophos (100%) and dicholorovas (66.63%) compounds being associated with very high mortality. Dimethoate was the commonest substance incriminated (18.75%). Conclusions: Organophosphorus poisoning has affected the young, productive males prominently. Higher severity of the disease process at presentation leads to significant mortality. Selective prohibition of the riskier compounds causing higher proportion of deaths is recommended.